CTIM-07. A PHASE I/II STUDY EVALUATING THE SAFETY AND EFFICACY OF A NOVEL LONG-ACTING INTERLEUKIN-7, NT-I7, FOR PATIENTS WITH NEWLY DIAGNOSED HIGH-GRADE GLIOMAS AFTER CHEMORADIOTHERAPY. (12th November 2021) - Campian, Jian; Butt, Omar; Luo, Jingqin; Avvaru, Chandini; Katumba, Ruth; Zhou, Alice; Kim, Albert; Dunn, Gavin; Abraham, Christopher; Yang, Se Hwan; Fan, Jean; Lee, Byung Ha; et al.
Abstract: BACKGROUND: Lymphopenia is common after standard radiation therapy (RT) and temozolomide (TMZ) in high-grade gliomas (HGG) and correlates with shorter survival. Interleukin-7 (IL-7), a T-cell proliferation cytokine, is inappropriately low in HGG patients. Our previous preclinical studies demonstrated that NT-I7 (efineptakin alfa), a recombinant human IL-7, corrects lymphopenia and improves survival in murine glioma models. This study examines the safety and absolute lymphocyte counts (ALCs) following administration of NT-I7 patients with newly diagnosed HGG. METHODS: Patients with HGG receiving RT/TMZ with ALC ≥600 were eligible. NT-I7 was administered intramuscularly within 1 week after completion of concurrent RT/TMZ and then every 12 weeks, for up to 4 total doses. Phase I examined 6 dose levels (60, 120, 240, 540, 720, and 960 mcg/kg) using the accelerated-titration design for the first 2 doses and 3 + 3 design thereafter to identify the maximum tolerated dose (MTD). Phase II is a double-blinded, placebo-controlled study with 10 HGG patients per arm comparing changes in ALC. Immune profiling will be performed with CyTOF and cytokine analysis. RESULTS: Phase I is complete, with 19 patients (89% GBM, median age: 58 (range: 25-78), median baseline ALC: 1000 cells/mm 3, median dexamethasone: 0 mg/day (range: 0-12)). The median number of NT-I7 doses administered was 2 (range: 2-4). The most common treatment-related adverse event was grade 1 or 2 injection site reactions (42%). Two patients had dose-limiting toxicities at 960 mcg/kg (grade 3 elevated alanine aminotransferase and grade 3 back pain), prompting selection of 720 mcg/kg for phase II. Dose-dependent increases in ALC were observed at 4 weeks ranging from 1.3x to 4.1x. Phase II enrollment is ongoing. CONCLUSIONS: NT-I7 is well tolerated when administered after chemoradiotherapy for HGG patients with MTD of 720 mcg/kg and demonstrates dose-dependent increase of ALC. Phase II and immune profiling are ongoing. Clinical Trial ID: NCT03687957.